The Usage and Limitations of Gene Therapy Versus Stem Cell Therapy for Myotonic Dystrophy Type 1 (DM1): Special Focus on Immune Response - Abdirasulova, Zhainagul Abdirasulovna; Jabbar, Basim Hanoon; Ismael, Sajida Hussein; Hussein, Ahmed M.; Saleh, Saad; Nazir, Nazarzoda Khusin (Trends in Immunotherapy, 2026)
Muscular dystrophies include myotonic dystrophy (MD). Although there is no cure for this disorder, many treatments can manage symptoms and reduce disease development. Standard pharmacological treatments and rehabilitation methods have largely failed, prompting researchers to investigate stem cell and gene therapy options. This review will discuss gene therapy and stem cell therapy as adjuvant therapies for MD, including their benefits, drawbacks, and timeline for implementation. We searched PubMed, Scopus, Web of Science (WOS), Cochrane Library, and Embase from 1980 to 2024 for preclinical and clinical gene therapy papers for MD using keywords such as "myotonic dystrophy" and "gene therapy." A search for "myotonic dystrophy" and "Stem Cell" yielded studies on stem cell treatment for MD. The initial search found 50 gene therapy and 38 stem cell research articles. Following our exclusion and filtering criteria, we deleted 31 articles on gene therapy and 23 articles on stem cells. We found 19 gene therapy publications and 15 stem cell-based publications. Antisense oligonucleotides (ASO), CRISPR technology, and AAV vectors have become the most popular methods. Induced pluripotent stem cells (iPSCs) and muscle-derived progenitor cells (MuSCs) were important cellular sources for investigation or application. Most research focuses on myotonic dystrophy type I (DM1). It is widely established that AAV vector-induced immune responses can affect the safety and efficacy of genetic therapy. Specific stem cells may also modulate MD patients' immunological responses, improving prognosis. Using cytokines and monoclonal antibodies as adjuvants to treat this complex illness is becoming more common.